EXPORT POTENTIAL OF UKRAINE AND ITS IMPLEMENTATION IN TRADE AND ECONOMIC RELATIONS WITH GERMANY - Атаманчук, Зорина; Носалюк, Назар (SWorldJournal, 2025)
The article summarizes the main approaches to revealing the content of the "export potential" category and provides relevant definitions proposed by domestic scientists. The situation with the Ukraine’s export potential at the current stage has been studi